EVALUATION OF THE EFFICIENCY OF GREEN-SYNTHESIZED SILVER NANOPARTICLES USING SALIX BABYLONICA LEAF EXTRACT FOR PAHS REMEDIATION - Al-Saeedi, Abeer Abdul Rahman Hanoon; Marhoon, Khitam Abbas (Journal for Technology and Science, 2026)
Objective: The study was conducted in the laboratories of the College of Science at Al-Qadisiyah University. Its aim was to evaluate the efficiency of silver nanoparticles (AgNPs) manufactured using a green process with an aqueous extract of willow leaves (Salix babylonica) and their use in the non-biological treatment and removal of polycyclic aromatic hydrocarbons (PAHs) from contaminated soil. These compounds are highly toxic and difficult to remove, posing a significant threat to the environment. The study included an evaluation of the removal efficiency of Naphthalene, Acenaphthene, and Pyrene. Method: The prepared nanoparticles were characterized using UV-Vis, XRD, SEM, and FTIR techniques, which confirmed the successful reduction of silver ions and the formation of highly stable spherical nanoparticles. The experiments involved treating industrially contaminated soil with different concentrations of silver nanoparticles (0.1, 0.01, and 0.001 mg/L), and the treatment was monitored for a period of 7 days. Results: The treatment results showed significant variation in removal rates depending on the nanoparticle concentration, with the highest removal rates of PAHs being recorded at a concentration of 0.1 mg/L. Novelty: The study concludes that the green manufacturing of silver nanoparticles using willow leaf extract represents an economical, efficient and environmentally friendly technique for treating soils contaminated with PAHs while preserving and improving soil properties.